Access to public information in Argentina with particular reference to personal and institutional data protection - Bellochio, Lucía (A&C - Revista de Direito Administrativo & Constitucional, 2017)
The article presents the legal framework for the right of access to public information in Argentina, its exceptions and the protection of personal and institutional data, analyzing the National Bill of Access to Public Information and the case law of the Supreme Court of Argentina.